2019
DOI: 10.1093/nar/gkz209
|View full text |Cite|
|
Sign up to set email alerts
|

Setting boundaries for genome-wide heterochromatic DNA deletions through flanking inverted repeats in Tetrahymena thermophila

Abstract: Eukaryotic cells pack their genomic DNA into euchromatin and heterochromatin. Boundaries between these domains have been shown to be set by boundary elements. In Tetrahymena , heterochromatin domains are targeted for deletion from the somatic nuclei through a sophisticated programmed DNA rearrangement mechanism, resulting in the elimination of 34% of the germline genome in ∼10,000 dispersed segments. Here we showed that most of these deletions occur consistently with very limited variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
5
9
0
Order By: Relevance
“…Different levels of coupling between DNA cleavage and DSB repair may exist in the related ciliate Tetrahymena thermophila. In this species, the vast majority of IESs are excised by Tpb2 [41], a Pgm-related domesticated transposase that introduces DSBs at variable positions around IES boundaries [42], which results in micro-heterogeneous IES excision junctions [43]. T. thermophila encodes a single bona fide Ku80 protein and the closure of its IES excision sites also depends upon the classical NHEJ pathway [44].…”
Section: Functional Specialization Of Ku80 Paralogs Enables Precise Dmentioning
confidence: 99%
“…Different levels of coupling between DNA cleavage and DSB repair may exist in the related ciliate Tetrahymena thermophila. In this species, the vast majority of IESs are excised by Tpb2 [41], a Pgm-related domesticated transposase that introduces DSBs at variable positions around IES boundaries [42], which results in micro-heterogeneous IES excision junctions [43]. T. thermophila encodes a single bona fide Ku80 protein and the closure of its IES excision sites also depends upon the classical NHEJ pathway [44].…”
Section: Functional Specialization Of Ku80 Paralogs Enables Precise Dmentioning
confidence: 99%
“…In Tetrahymena, flanking sequences are known to have a significant role in the elimination of a number of IESs [ 70 , 71 ]. Together, Lia3p and Lia3-Like 1 (LTL1) regulatory proteins interact with flanking regulatory sequences to determine MDS–IES boundaries for several IESs for excision [ 72 74 ]. These data highlight the importance of both IES pointer sequences and their flanking regions in identifying MDS–IES boundaries.…”
Section: Nuclear Dimorphism In Ciliatesmentioning
confidence: 99%
“…It was known that cis -acting sequences helped to guide the excision from experiments in which shifting of certain IES-flanking sequences led to shifting of excision boundaries, but these sequences varied from IES to IES and no common consensus could be found [ 73 , [77] , [78] , [79] ]. Recently, a genomewide approach to search for IES-flanking IR sequences was undertaken, and it was found that there are several conserved IR sequences that flank different subsets of IESs at similar distances on both sides of the IES [ 80 ]. The known IES boundary-defining protein LIA3 was found to aid in the excision of a subset of IESs, and these LIA3-dependent IESs share similar polypurine-rich IR sequences at their boundaries [ 80 , 81 ].…”
Section: Excisases and Their Requirementsmentioning
confidence: 99%
“…Recently, a genomewide approach to search for IES-flanking IR sequences was undertaken, and it was found that there are several conserved IR sequences that flank different subsets of IESs at similar distances on both sides of the IES [ 80 ]. The known IES boundary-defining protein LIA3 was found to aid in the excision of a subset of IESs, and these LIA3-dependent IESs share similar polypurine-rich IR sequences at their boundaries [ 80 , 81 ]. Meanwhile, a second boundary-defining protein, Ltl1, was found to be required for the excision of another subset of IESs.…”
Section: Excisases and Their Requirementsmentioning
confidence: 99%